Genomic characterization of four novel bacteriophages infecting the clinical pathogen Klebsiella pneumoniae. (13th August 2021) - Bonilla, Estrada; Costa, Ana Rita; van den Berg, Daan F; van Rossum, Teunke; Hagedoorn, Stefan; Walinga, Hielke; Xiao, Minfeng; Song, Wenchen; Haas, Pieter-Jan; Nobrega, Franklin L; Brouns, Stan J J
Abstract: Bacteriophages are an invaluable source of novel genetic diversity. Sequencing of phage genomes can reveal new proteins with potential uses as biotechnological and medical tools, and help unravel the diversity of biological mechanisms employed by phages to take over the host during viral infection. Aiming to expand the available collection of phage genomes, we have isolated, sequenced, and assembled the genome sequences of four phages that infect the clinical pathogen Klebsiella pneumoniae: vB_KpnP_FBKp16, vB_KpnP_FBKp27, vB_KpnM_FBKp34, and Jumbo phage vB_KpnM_FBKp24. The four phages show very low (0–13%) identity to genomic phage sequences deposited in the GenBank database. Three of the four phages encode tRNAs and have a GC content very dissimilar to that of the host. Importantly, the genome sequences of the phages reveal potentially novel DNA packaging mechanisms as well as distinct clades of tubulin spindle and nucleus shell proteins that some phages use to compartmentalize viral replication. Overall, this study contributes to uncovering previously unknown virus diversity, and provides novel candidates for phage therapy applications against antibiotic-resistant K. pneumoniae infections.